RANCANG BANGUN APLIKASI OBJEK WISATA BENTENG ROTHERDHAM BERBASIS VIRTUAL REALITY 360 - Ardiansyah; Hamdan Arfandy; Hendra Surasa (STMIK KHARISMA Makassar, 2021)
The purpose of this study is to make the application of Rotherdam castle attractions based on Virtual Reality 360. The benefit of this research is that it can provide a useful reference for the academic world, especially in research to be carried out by researchers who will come in terms of technological developments in the reality of Virtual Reality. In this application there is one user, the user who will use this application to get information about Benteng Rotherdam, as well as 360 virtual reality images. The function of the user in addition to using the application, the user can also add images and information of Rotherdam Fortress. Another function of this application is that people who will visit the Rotherdam can get references about the Rotherdam . And they can also see the shape of the from the application from outside the or inside the fortress Rotherdam. The author has succeeded in making the Rotherdam attraction based on Virtual Reality 360˚. Based on black box testing, the application runs according to what the authors expect.